A Comparison of Ulexite Mineral and Borax Decahydrate to Synthesize Zinc Borate - Piskin, M. B.; Acarali, N. Baran (INT ASSOC ENGINEERS-IAENG, 2010)
The purpose of this study is to compare the zinc borate results by using ulexite mineral and borax decahydrate. Zinc borate production was carried out by using boric acid synthesized in first stage, zinc oxide and commercial zinc borate as seed. In second stage, zinc borate samples produced were filtered, dried at 105 degrees C for 20 h. The effect of reaction time, H3BO3/ZnO ratio, seed on yield have been investigated. X-ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) analysis showed that zinc borate was synthesized successfully.
Keywords: Borax decahydrate; ulexite; zinc borate; KINETICS; ACID; Engineering